The Effect Of Puzzle Games On Reducing Impulsive Behavior In Hyperactive Children Aged 5-6 Years - Sri Puspita Wulandari Paputungan; Ardini, Pupung Puspa; Sutisna, Icam (JURNAL PENDIDIKAN USIA DINI, 2025)
The study problems are: "Is there a significant effect of puzzle games on reducing impulsive behavior in hyperactive children aged 5-6 years at TK Al-Khairat Kindergartens, Gorontalo City?" The study aims to determine the impact of puzzle games on reducing impulsive behavior in hyperactive children aged 5-6 years at TK Al-Khairat Kindergartens, Gorontalo City. The study employed a quantitative approach using an experimental method with a pre-test and post-test design, where tests were conducted before and after the treatment. The subjects were four hyperactive children aged 5-6 years in Group B at TK Al-Khairat Kindergarten, Gorontalo City. The study focused on reducing impulsive tendencies in hyperactive children through puzzle games. Data collection for the pre-test and post-test was conducted using research instruments and analyzed statistically. The results showed a significant difference in hyperactive children's average impulsive behavior scores before and after the intervention, with pre-test and post-test scores of 16.00 and 23.50, respectively. The findings confirm a significant effect of the intervention. The t-test results showed a sig. (2-tailed) value of 0.000 < 0.05, leading to the rejection of H0 and acceptance of H1. It can thus be concluded that there is a significant difference in impulsive behavior between the pre-test and post-test data, indicating that the X variable significantly affects the y variable.